2015
DOI: 10.15441/ceem.15.085
|View full text |Cite
|
Sign up to set email alerts
|

Preventable trauma death rate in Daegu, South Korea

Abstract: ObjectiveThis study investigated the preventable death rate in Daegu, South Korea, and assessed affecting factors and preventable factors in order to improve the treatment of regional trauma patients.MethodsAll traumatic deaths between January 2012 and December 2012 in 5 hospitals in Daegu were analyzed by panel review, which were classified into preventable and non-preventable deaths. We determined the factors affecting trauma deaths and the preventable factors during trauma care.ResultsThere were overall 358… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…[1][2][3][4][5] Although several investigations on preventable trauma deaths have been conducted since the 1990s, few studies have been conducted on the timing of deaths in Korea. [6][7][8][9][10] This could be due to the lower rate of autopsies conducted in the country. 12 However, the main reason was that no basis has been established for in-depth analysis and investigation on trauma deaths due to the lack of a trauma system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5] Although several investigations on preventable trauma deaths have been conducted since the 1990s, few studies have been conducted on the timing of deaths in Korea. [6][7][8][9][10] This could be due to the lower rate of autopsies conducted in the country. 12 However, the main reason was that no basis has been established for in-depth analysis and investigation on trauma deaths due to the lack of a trauma system.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Moreover, previous studies on preventable trauma deaths in Korea tended to focus on determining the preventability of death and calculating mortality rates. [6][7][8][9][10] These studies did not investigate in detail the timing of death, mechanism of injury, and cause of death. As a result, the trauma system in Korea has not yet reached a level that is high enough to draw corrective action plans or injury prevention programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When mortality occurred before 3 months, this was described as mortality at 3 months. The preventable death rate was also investigated and defined as (preventable death/total death)×100 [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…In particular, trauma patients have a high socioeconomic loss due to high mortality rates at the age of production. The socioeconomic cost of trauma was estimated at about 13.7 trillion KRW in 2003, and the ratio of loss of productivity due to damage deaths in total socioeconomic cost was 60.2-62.4%, respectively [2]. One study reported in 2006 found that the cost of production loss per trauma death was about 350 million KRW.…”
Section: Introductionmentioning
confidence: 99%